244-year long tree-ring based drought records from Uttarakhand, western Himalaya, India. (20th October 2021) - Yadava, Akhilesh K.; Misra, Krishna G.; Singh, Vikram; Misra, Sandhya; Sharma, Yogesh K.; Kotlia, Bahadur S.
Abstract: Droughts in the orography dominated mid-to-high elevation Himalaya have serious impact on the agrarian economy and biodiversity of the region. Temporally and spatially limited weather records from the Himalaya restrict our understanding on the socioeconomic impact of droughts in long-term perspective. In view of this, high-resolution proxies are required to develop long-term drought records from the data scarce Himalayan region. To fill this void, we developed February–May (FMAM) 4-month standardized precipitation-evapotranspiration index (SPEI4-May), a metric of drought, extending back to AD 1773 using ring-width chronology of Himalayan cedar ( Cedrus deodara (Roxb.) G. Don) from Chakrata region of Garhwal, Uttarakhand, western Himalaya. The calibration model (1969–2016) captured 43% of the variance in the observed SPEI series. The SPEI reconstruction revealed high year-to-year and inter-decadal variation with 1774 (SPEI -3.11) and 1787 (SPEI +2.13) being the driest and the wettest years, respectively. The five year mean of reconstructed SPEI revealed droughts in 1818–1822, 1798–1802, 1813–1817, 1793–1797, 1958–1962 and pluvials in 1783–1787, 1838–1842, 1788–1792, 1933–1937, 1808–1812. A comparison of present SPEI reconstruction with other available tree-ring based precipitation and drought records from the western Himalayan region revealed synoptic scale features represented in our data. The findings underscore that a wide network of such large tree-ring based drought records from the data scarce Himalayan region should be very useful to understand the spatial distribution of droughts.